Effects of Thermal Manipulation and Serotonin Modulation on Brain HSP70 and HSP90 Gene Expression in Late Embryogenesis of Broilers - Hamed KHasti; Ladan Emadi; Shahrzad Azizi; Elham Mohammadi; Hadi Tavakkoli (Veterinary Medicine and Science)
ABSTRACT Introduction Broiler chickens are particularly vulnerable to elevated temperatures compared to mammals because they have feathers instead of sweat glands, undergo rapid growth and are intensively bred in commercial systems. Serotonin, as neurotransmitter, is essential for the development of the embryonic brain and neural functions, helping the body adapt to difficult environments such as heat stress (HS) that broiler chickens are susceptible to by regulating physiological and metabolic processes. Heat shock proteins, which are produced in response to different types of stress, protect cells from damage. This research seeks to investigate the effect of HS on the cellular stress response in embryonic brain tissues, with a particular emphasis on the role of serotonin. Methods A total of 120 fertilized eggs were randomly divided into control and serotonin (20 µg/egg) groups. Before incubation, serotonin solution or normal saline (0.9% NaCl) was injected into the albumen. On the 13th day of the experiment, subjects were divided into groups exposed to either high or normal temperature conditions. The HS groups were initially exposed to 39.5°C for 2 h, with the exposure duration increasing by 2 h each day until the 17th day of incubation, culminating in 10 h of HS on the final day. On the 18th day, brain samples were collected for histopathological examination and mRNA expression analysis of HSP70 and HSP90. Results HS significantly reduced the gene expression of HSP70 and HSP90 in embryonic brain tissue. However, the presence of serotonin under stress conditions significantly increased the expression of these heat shock proteins compared to the HS group alone. Conclusion This study is the first to report decreased gene expression of brain HSP70 and HSP90 in Ross broiler embryos under HS, with serotonin serving as an anti‐stress agent by promoting HSP gene expression. Further research is necessary to explore the effects of serotonin on heat tolerance and chick performance post‐hatching.